Anti-PL-7 antibody-positive dermatomyositis with progressive interstitial pneumonia complicated with tracheal ulcer. (2021) - Sato, Shintaro; Yamakawa, Hideaki; Takemura, Tamiko; Nakamura, Tomohiko; Oba, Tomohiro; Nishizawa, Tomotaka; Kawabe, Rie; Akasaka, Keiichi; Amano, Masako; Matsushima, Hidekazu
Abstract: Tracheobronchial lesions are rare extramuscular complications for idiopathic inflammatory myopathies including dermatomyositis. We herein report a 65-year-old woman with tracheal ulcer during the progression of dermatomyositis-associated interstitial lung disease. Treatment with corticosteroids combined with immunosuppressive agents resulted in improvement of the tracheal ulcer and pulmonary involvement. We believe that the tracheal ulceration might reflect the disease behaviour of dermatomyositis and dermatomyositis-associated interstitial pneumonia.